URANIUM-SERIES DISEQUILIBRIUM, SEDIMENTATION, DIATOM FRUSTULES, AND PALEOCLIMATE CHANGE IN LAKE BAIKAL - Edgington D.N.; Gustin M.P.; Robbins J.A.; Colman S.M.; Orlandini K.A. (My University, 1996)
The large volume of water, approximately one-fifth of the total surface fresh water on the planet, contained in Lake Baikal in southeastern Siberia is distinguished by having a relatively high concentration of uranium (ca. 2 nM), and, together with the surface sediments, an unusually high234U238U alpha activity ratio of 1.95. About 80% of the input of uranium to the lake, with a234U238U ratio of 2.0, comes from the Selenga River. Profiles of uranium, as well as the extent of isotopic disequilibrium in a 9 m sediment core collected on Academic Ridge, generally show high values during interglacial periods corresponding to high diatom frustule numbers (DiFr) and biogenic silica (BSi) data that have been reported elsewhere. During glacial periods (low DiFr and BSi), uranium progeny (234U and230Th) were in secular equilibrium with low concentrations of their parent238U. Radionuclide distributions were interpreted in terms of a quantitative model allowing for adsorption of riverine inputs of uranium onto two classes of sedimenting particles with differing238U232Th ratios and uranium progeny in secular equilibrium. If the234U238U activity ratio of adsorbed uranium has remained constant, mean sedimentation rates can be independently estimated as 3.6 ± 0.6 and 3.7 ± 0.9 cm · kyr−1 for the decay of234U and in-growth of230Th, respectively. These rates are consistent with a mean rate of 3.76 cm · kyr−1, calculated by optimization of the correspondence between adsorbed238U and δ18O in dated oceanic sediments. The adsorbed uranium apparently tracks variable river flow during interglacials and is drastically reduced during periods of glaciation. Evidently, uranium has not been significantly redistributed within Baikal sediments over at least the past 250 kyr and is a unique, biologically non-essential, tracer for climate-sensitive processes, which provide their own internal geochronometers, potentially useful for ages up to 1 Myr BP.